Characterization of Antibiotic-Resistance Antarctic Pseudomonas That Produce Bacteriocin-Like Compounds - Tello-Reyes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In this study, bacterial isolates C1-4-7, D2-4-6, and M1-4-11 from Antarctic soil were phenotypically and genotypically characterized, and their antibacterial spectrum and that of cell-free culture supernatant were investigated. Finally, the effect of temperature and culture medium on the production of antimicrobial compounds was investigated. The three bacteria were identified as different strains of the genus Pseudomonas. The three bacteria were multi-drug resistant to antibiotics. They exhibited different patterns of growth inhibition of pathogenic bacteria. M1-4-11 was remarkable for inhibiting the entire set of pathogenic bacteria tested. All three bacteria demonstrated optimal production of antimicrobial compounds at 15 °C and 18 °C. Among the culture media studied, Nutrient broth would be the most suitable to promote the production of antimicrobial compounds. The thermostability exhibited by the antimicrobial molecules secreted, their size of less than 10 kDa, and their protein nature would indicate that these molecules are bacteriocin-like compounds. © 2024 by the authors.